(untitled) (The Chittagong University Journal of Business Administration, 2025)
South Asia is one of the world’s least economically integrated developing regions and every country is increasing its maturity. This economic expansion, nevertheless, degrades the environment and creates an environmental Kuznets curve (EKC). The principal aim of this paper is to ensure the presence of EKC and its current phase in South Asia. Applying the idea of ecological footprint which exceeds the threshold value and so negative, as a proxy variable of environmental degradation instead of carbon-dioxide emission on economic structuration. By using the ARDL method and time-varying causality test with the secondary data from 1975-2019 (systematically recorded environmental data frame), this paper supports the presence of EKC curve yet in the first phase- a gradual increase, for the South Asian region. The empirical findings suggest that real GDP, trade openness, and urbanization from the first lag are degrading the environment whereas efficient energy, globalization, and urbanization at the level estimates are upgrading this situation. Therefore, this paper suggests pro-environment criterion for urbanization, decoupling by service economies, massive implementation of no regret technologies, trade openness and globalization for advanced and green investors.